Investigation of low coherence interferometry techniques for biomedical applications - Chow, Tzu Hao (2014)
Interferometric techniques have been used as imaging techniques in many applications. In using low coherence sources in interferometry, good axial resolution can be achieved. The objective of this thesis is to investigate the use low coherence interferometry in biomedical applications. Low coherence interferometry (LCI) was incorporated into an optical tweezers system to determine the trapping dynamics. An optical coherence tomography (OCT) system based on LCI principles was designed and implemented to detect virus infection in orchid leaves. The OCT system was then modified to realize a high-speed endoscopic OCT imaging system. A numerical method and a common-path probe design were investigated to address the issue of loss of axial resolution due to dispersion. Optical tweezers typically use back-focal interferometry to determine the position of an object in the optical trap. Extensive initial calibration is needed before accurate positional measurements can be made. A LCI system, on the other hand, can provide accurate axial measurements with minimal calibration. A common-path LCI system was incorporated into an optical tweezers system. The light beams of LCI and optical tweezers are collinear, thereby ensuring a good axial accuracy. The trapping dynamics of a trapped microsphere under different trapping conditions were investigated. The results demonstrated that LCI is a viable alternative to back-focal plane interferometry in determining the trapping dynamics. A spectral domain optical coherence tomography (SD-OCT) system was designed and built to identify virus infection in orchid plants. Besides revealing the cross-sectional structure of orchid leaves, a highly scattering upper leaf epidermides were detected with OCT for virus-infected plants. This distinct feature is not observable under histological examination of the leaf samples. The results suggest that virus-infected orchid plants can be accurately identified by imaging the epidermal layers of its leaves with OCT, thereby potentially leading to a better control on the spread of viruses in the orchid industry. In vivo imaging of human tissues has given valuable insights into the understanding of diseases and their management. Conventional in vivo imaging involves white-light endoscopy which relays the optical image of tissue surface back to the user. By contrast, OCT allows the imaging of tissue a few millimeters below the tissue surface which provides additional information on the tissue structure. A gradient-index (GRIN) rod probe was designed and incorporated into a nasopharyngeal rigid probe for both OCT and white-light imaging. To capture an image with minimal motion blur, a fast spectrometer was designed with high spectral resolution. The results showed that there is sufficient resolution in the overall endoscopic OCT probe system to pick out sweat ducts beneath a human skin. The axial resolution of the OCT system depends on the bandwidth of the light source. However, dispersion mismatches between the sample and reference arms of the interferometer broadens the axial point spread function which worsens the axial resolution. A numerical technique was used to extract the phase of the interferogram which is then applied to offset any systemic dispersion mismatches in the system. The results showed that the numerical technique is effective in recovering the OCT image with dispersion. A common path probe with an axicon tip was also proposed to combat dispersion. The axicon tip allowed imaging of a few millimeters without significant loss of resolution due to the diffraction-free properties. The common-path design minimized dispersion and polarization mismatches. OCT images with good axial resolution and imaging depth were obtained with this probe.